Failure Probability Analysis of Levees Affected by Mammal Bioerosion. Issue 12 (8th December 2021) - Balistrocchi, Matteo; Moretti, Giovanni; Ranzi, Roberto; Orlandini, Stefano
Abstract: Mammal bioerosion is an emergent threat to the functionality of levees. In the present paper, the problem of assessing the failure probability of levees affected by mammal bioerosion is addressed. A fully bivariate description of peak flow discharge and flood duration is combined with a deterministic unsteady seepage flow model to obtain a suitable model of variably disturbed levee response to the observed natural variability of floods. Monte Carlo analysis is also implemented to evaluate the epistemic uncertainty connected to the description of the river system. The obtained model is tested with respect to a real‐world levee located along the Secchia River in northern Italy, which underwent a disastrous failure caused by mammal bioerosion in 2014. The convex linear combination of two Archimedean copulas is found to fit the empirical dependence structure between peak flow discharge and flood duration. The reliability of the unsteady seepage flow model is tested against detailed numerical simulations of the seepage occurring through the levee body. A limit state function is obtained by comparing the maximum extent of the seepage front to the distance between the den end and the riverside levee slope, and the corresponding levee safety and failure regions are delimited. Results obtained from the developed model reveal a significant impact of mammal dens located near the levee crest in terms of failure probability and related return period. This impact is consistent with failures observed in the study area. Plain Language Summary: Burrowing mammals often find in levees a suitable habitat. Unfortunately, mammal dens can significantly compromise the functionality of levees by creating preferential flow paths for flood water seeping through the levee bodies, and by causing ultimately levee failures due to excessive seepage and internal erosion. In fact, many levee failures have been connected to the levee weakening caused by mammal dens. Mammal bioerosion significantly increases the failure probability of levees and the related flood risk in densely populated floodplains. Estimating the failure probability of levees affected by mammal bioerosion is therefore a relevant societal need. In the present study levee, safety and failure conditions are estimated by combining a fully bivariate statistical description of peak flow discharge and flood duration with a computationally efficient unsteady seepage flow model. The resulting modeling framework incorporates the natural variability of floods and the essential hydraulic properties of disturbed/undisturbed levees. Model results reveal that the return period of levee failure due to excessive seepage reduces from 100 to 9 years, namely of −91%, when the mammal den extends for 84% of levee thickness. These results can be used to inform levee design and maintenance programs for the safety of societies living in floodplains worldwide. Key Points: Fully bivariate analysis of peak flow discharge and flood duration is used to describe the hydrologic forcing to levees Vorogushyn et al.'s unsteady seepage flow model is extended to derive the failure probability of variably disturbed levees Return period of levee failure due to excessive seepage reduces from 100 to 9 years when the mammal den extends for 84% of levee thickness